Experimental and numerical study using ANFIS - neuro fuzzy model on heat pipe heat exchanger. (2022) - Ramkumar, P.; Vivek, C.M.; Ramasamy, S.; Kajavali, A.; Sivasubramanian, M.
Abstract: In the electronic cooling systems and utilization of waste heat safeguard the electronic components and life. This study focus on the experimentation and numerical comparision of an Heat Pipe Heat Exchanger (HPHE) using acetone. The investigation focuses on various orientation angles (0° and 90°) and extended with (10° to 80°) angles. The investigation results proves that the maximum thermal performance is obtained at 0° than 90°, similarly for other angles the 60° shows higher peformance than 10° to 80° angle. The minimum thermal resistance obtained as 5.76% for 60° while related with 10°. The observed average thermal resistance for experimental value as 1.79% and predicted value as 1.71%. From the investigation it's evident that experimental results are closes to the numerical valuses using ANFIS - Neuro fuzzy system. In the utilization of waste heat recovery system the HPHE shows better performance for cooling of electronic system.